The Relationship between Philosophy, Balaghah, and the Qur'an: A Study of Manahij Tajdid fi an-Nahwi wa al-Balaghah wa at-Tafsir wa al-Adab by Amin Al-Khuli - Abdurrahman, Ja'far Rais; Zenrif, M. Fauzan (Kitabina: Jurnal Bahasa dan Sastra, 2023)
This paper discusses Amin Al-Khuli's views on the Science of Balaghah and its relationship with the sciences of Philosophy and Psychology, as well as highlighting manipulation in the Qur'an. This research focuses on the relationship between Balaghah and Psychology, using the library research method. The author uses the book "Manahij Tajdid fi An-Nahwi wa Al-Balaghah wa At-Tafsir wa Al-Adab" as the main reference, accompanied by various relevant literature sources. The analysis was conducted to understand the implications of philosophy's relation to Balaghah Science, psychological manipulation in the Qur'an, as well as ideas and examples of psychological exposure in Islamic sacred texts. In this study, researchers found that Balaghah and Psychology are interrelated. The concept of Balaghah which includes the use of language and rhetoric in the Qur'an can affect the psychology of the reader. Psychological manipulation in the Qur'an is also found in the form of the use of language and rhetoric that aims to influence readers. However, the researcher emphasizes that such manipulation is not negative, but rather an attempt to help the reader understand the Qur'ānic message better. This research provides substantial insight into understanding the Qur'an from the perspective of Balaghah and Psychology. The library research method used allows the researcher to gain a deeper understanding of Amin Al-Khuli's views and provides a clear picture of the relationship between Balaghah and Psychology. Thus, this study can be an important reference for researchers and readers who are interested in understanding the Qur'an from this perspective.